21세기 다발골수종의 단일 기관 현실 세계 경험 - 조형우; Hyungwoo Cho; 김신; Shin Kim; 이경민; Kyoungmin Lee; 강은희; Eun Hee Kang; 박정선; Jung Sun Park; 서철원; Cheolwon Suh (The Korean journal of medicine, 2022)
목적: 21세기 들어 우리나라 다발골수종 발생 수가 급속히 증가하고 있으며, 진단 기준이 새로워지고, 신약이 계속 개발 적용되고 있다. 이에 최근 15년여 동안 서울아산병원에서 진단한 다발골수종 환자들의 현실 세계 경험을 분석 보고한다. 방법: 다발골수종 환자 사항들을 전향적으로 기록한 서울아산병원 다발골수종 등록 자료를 이용하였다. 탈리도마이드 투여가 가능해진 2003년부터 2년 생존 자료를 얻을 수 있는 2019년 4월 사이에 진단된 774명의 다발골수종 환자를 대상으로 하였다. 자가 조혈모세포 이식술 시행 가부가 정해지는 65세를 기준으로 나누어 각 군의 특성을 분석하였다. 연도군은 보르테조밉이 가용해진 2006년, 레날리도마이드가 보험 적용되는 2010년을 기준으로 나누어 살폈다. 결과: 65세 미만 환자군이 65세 이상군보다 양호한 예후 인자를 갖고 있었다. 호주/뉴질랜드의 골수종 및 연관 질환 등록 자료 보고와 비교할 때 의미 있는 인종적, 지리적 차이를 보이지 않았다. 전체 환자의 중앙 생존 기간은 3.7년, 5년 전체 생존율은 41.8%, 10년 생존율은 23.4%였다. 65세 미만군이 65세 이상군보다 생존 성적이 우수하였고, 시대가 흐름에 따라 생존 성적이 계속 향상되었다. 전체 환자군에서 연령, 수행 능력, 신 기능, 혈청 C-반응단백 수치, 혈청 젖산탈수소 효소 수치, 염색체 이상 등이 의미 있는 예후인자들이었다. 결론: 이 보고는 21세기 초, 대한민국의 한 3차 기관에서 새로이 진단한 다발골수종 환자들의 현실 세계 경험을 보여준다. Background/Aims: The incidence of multiple myeloma (MM) in Korea is rapidly increasing. The diagnostic criteria of MM have been updated and novel therapeutic agents are available. This study explored the features of MM patients registered at Asan Medical Center (AMC) and the outcomes over the past 15 years. Methods: Data were obtained from the AMC MM registry, which has been collecting the data of MM patients prospectively. The 774 MM patients included in our analysis were diagnosed from 2003, when thalidomide became available as a novel therapeutic agent, until April 2019. The 2-year survival rate of these patients was assessed. Patients were divided into two groups based on whether they were older or younger than 65 years, which is the cutoff age for the indication of autologous stem cell transplantation. Patients were also grouped according to the year of diagnosis: up to 2006, when bortezomib became available, and up to 2010, when the cost of lenalidomide was reimbursed. Results: Patients < 65 years of age had better prognostic features, including a better performance, less advanced disease stage, and fewer abnormalities in their fluorescent in-situ hybridization (FISH) analysis results. A comparison of our Korean patients with patients registered in the Myeloma Related Disorder Registry data of Australia and New Zealand, showed ethnic discrepancies. The median overall survival of all patients was 3.7 years, with a 5-year survival rate of 41.8% and a 10-year survival rate of 23.4%. Survival progressively improved in patients diagnosed later. Age, performance status, renal function, C-reactive protein level, lactate dehydrogenase level, and cytogenetic findings were identified as significant prognostic factors. Conclusions: This real-world survey revealed the clinical features and survival rates of patients at a tertiary Korean Hospital who were diagnosed with MM at the beginning of 21st century. (Korean J Med 2022;97:125-140)